PELATIHAN MANAJEMEN STRES UNTUK KESEJAHTERAAN PASIEN HIPERTENSI - Sulistyarini, Indahria; Adha, Angga Aldino Apriawan; Maulina, Nuzul Putri (JIP (Jurnal Intervensi Psikologi), 2023)
Hypertension is a chronic disease with a growing prevalence that can adversely impact the wellbeing of individuals affected. This study aims to investigate the influence of stress management training on the wellbeing of hypertensive patients. The study included 10 subjects, divided into 5 experimental groups and 5 control groups. The stress management training utilized in this research was developed by Taylor. Two measurement instruments were employed: Positive and Negative Affect Schedule with 20 items and Satisfaction with Life Scale with 5 items for subjective wellbeing. Additionally, psychological wellbeing was measured using Ryff's wellbeing scale, as developed by Prameswari. The research findings indicate that stress management training has an effect on subjective wellbeing but not on psychological wellbeing. Stress management training assists participants in remaining calm and stress-free when confronted with challenges.